People’s Perceptions about the Socio-Economic and Environmental Impact of Coastal Green Belt in Bangladesh - Tanmoy Dey; Md. Golam Morshed Rajib; Md. Akramul Islam (CV. Literasi Indonesia, 2021)
Understanding the perceptions and attitudes of local people towards afforestation is crucial for successful afforestation. To better understand the people's perceptions about the coastal green belt, we surveyed the Satkhira and Bhola districts during January 2021. A questionnaire survey of 200 respondents was conducted by a purposive and random sampling technique to obtain quantitative data. On the other hand, two Focus Group Discussions (FGDs) were performed to obtain qualitative data based on the diversity of age, sex, education, and occupation variables. We used to evaluate the respondent’s perceptions about the coastal green belt by 5-point Likert scale data. The majority portion of the people in our study area was poor and their profession was fisherman and housewife among males and women respectively. The majority of them agreed that the green belt helped them in numerous ways, to rear their cattle and built a house near the green belt, by promoting the growth of crops, and further protect them from different natural calamities by reducing wind velocity. Shelterbelts greatly enhance tourism in that area, improved communication facilities, and increase their socio-economic condition and values. Shelterbelt has long-term benefits, peoples have positive attitudes towards shelterbelt and they seek training to maintain this shelterbelt smoothly. Respondents wanted fruit tree species as shelterbelt species near the embankment. This information can be used for policy formulation in terms of successful plantation by considering people’s attitudes, which may work in both mitigation and adaptation of climate change in the coastal remote areas of Bangladesh.